MULTICRITERIA EVALUATION OF SUSTAINABILITY IN LAST-MILE LOGISTICS: A REVIEW - Franco Corti; Chiara D’Alpaos; Luciano Greco (Valori e Valutazioni)
As cities continue to grow, there is a pressing need to enhance the quality of life for citizens while also tackling challenges such as the rising demand for urban freight deliveries and environmental sustainability goals. However, the competition between people and goods for limited space in urban areas creates pressure on local authorities and piques the interest of consultants and researchers. This study examines how sustainability is tackled when decisionmakers and stakeholders assess alternative solutions with multi-criteria methods in different urban logistics contexts. A multi-step systematic review has been performed to examine the use of multi-criteria analysis in the specific multidisciplinary sector of urban freight logistics and how sustainability is defined and pursued by identifying 56 papers published between 2011 and 2023addressing problems related to sustainable urban logistics solutions. Despite the growing number of applications and scientific publications, a standard methodological framework is lacking in selecting methods and criteria to evaluate sustainable logistics solutions. To fill this gap, this paper aims to map the problems addressed and the methods applied, the stakeholders involved as actors, their objectives, and the criteria chosen to support their choices. This paper investigates the decision-making process, actors and sources, and which criteria are chosen when the intent is to pursue sustainable solutions. Future research could delve deeper into the weighting process among criteria to elucidate the coherence between stated goals and actual decisions. Such research could offer valuable insights into how decisions are made and help identify areas for improvement.